THE USING OF SURVEY, QUESTION, READ, RECITE, REVIEW METHOD (SQ3R) IN INCREASING THE ACTIVENESS AND ACHIEVEMENT IN ENGLISH SUBJECT. (Study in English Subject 9th Grade at SMPNegeri 06 Lebong) - Rahmi Utama; Turdjai Turdjai (DIADIK, 2019)
This research is conducted to describe the effect of SQ3R method toward students’ activeness and achievement in English subject of students at SMPNegeri 06 Lebong. This research was classroom action research and quasi experiment. In this research, an action research conducted collaboratively between researchers themselves as teachers of the school in question, and another teacher as an observer. In the action this study using SQ3R method to increase the activeness and achievement of students who have find still very low. The subjects of study were students of class IX.1 for action class room research and students of class IX.2 dan IX.3 for experiment research SMPN 06. The data was collected using activeness questionnaire, documentation, field notes and test results to learn. The data analysis technique used is descriptive qualitative analysis, which describes the data by using the phrase to obtain a clear and detailed description. The results of this study indicate that (1) the use of SQ3R method couldincrease the students’ activeness; (2) the use of SQ3R could increase the students’ achievements; (3) the effectiveness of the SQ3R method could increase the students’ achievement in English subject.